Isabelle's new friend - Brunhoff, Laurent de, 1925- (New York : Random House, 1990)
Isabelle the elephant and Vic the rhino persist in their controversial friendship, despite the bad feelings between their respective species.
"A Babar book"--Cover.
Accelerated Reader AR
Keywords: Elephants -- Fiction; Rhinoceroses -- Fiction; Prejudices -- Fiction